UJI KANDUNGAN KARBOHIDRAT PADA MIE SAGU BASAH - Fratama, Rizky Fratama; Aliwasa, Aliwasa; Ramadhan, Akmal; Cahyuda, Nazamri; Hetrik, Muhammad (PPPM POLTESA, 2024)
Carbohydrates are one of the ingredients found in food. Carbohydrates are one of the main groups of nutrients consisting of sugar, fiber, and starch. Carbohydrates play an important role as the main source of energy for the body, apart from being a source of energy carbohydrates have an important role in maintaining a healthy digestive system. The purpose of this carbohydrate test is to determine the carbohydrate content contained in wet sago noodles. This test method uses a quantitative method to determine the content contained in wet sago noodles. During the testing process using the Luff Schoorl method, which is a chemical technique used to determine the sugar content in samples, especially the carbohydrate content. The results obtained from 2 test samples, namely sample 1 as much as 28.595% and sample 2 obtained as much as 27.503%. The conclusion of the results of this test is to determine the carbohydrate content contained in wet sago noodles before being marketed to consumers. With the results of this carbohydrate test, it provides information about the high carbohydrate content in wet sago noodles.